1994
DOI: 10.1590/s0101-81751994000200001
|View full text |Cite
|
Sign up to set email alerts
|

Atratividade de diferentes iscas e sua relação com as fases de desenvolvimento ovariano em calliphoridae e sarcophagidae (insecta, diptera)

Abstract: ABSTRACT. ATTRACTIVENE'iS OF OIFFERENTS BAITS AND ITS RELATIONMatéria orgânica em decomposição, exalando odores característicos tem sido utilizada como isca para atrair dípteros caliptrados, sendo vasta a literatura referente à atratividade de diferentes iscas sobre esses insetos, inclusive na região Neotropical (FERREIRA 1978; UNHARES 1981a; LINHARES 1981b; D'ALMEIDA & LOPES 1983 ; CARVALHO el ai. 1984; D'ALMEIDA 1984; DIAS el ai. 1984; ALMEIDA 1985, entre outros). Esses dípteros podem utilizar as iscas qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…The latter showed complete rejection for human settlements in Campinas, SI=-71.10 (Linhares 1981), Belo Horizonte, SI=-93.00 (Dias et al 1984) and Rio de Janeiro, SI=-80.99 (D'Almeida 1984), with most individuals collected in the forest, it was classified as an asynanthropic species. In La Pintada, it showed a necrophagous behavior being attracted in a larger proportion by fish and chicken viscera, what coincides with the other studies (D'Almeida 1984, Barros et al 2008, D'Almeida & Lima 1994, while in Campinas it has been also reported in human faeces (Linhares 1981).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The latter showed complete rejection for human settlements in Campinas, SI=-71.10 (Linhares 1981), Belo Horizonte, SI=-93.00 (Dias et al 1984) and Rio de Janeiro, SI=-80.99 (D'Almeida 1984), with most individuals collected in the forest, it was classified as an asynanthropic species. In La Pintada, it showed a necrophagous behavior being attracted in a larger proportion by fish and chicken viscera, what coincides with the other studies (D'Almeida 1984, Barros et al 2008, D'Almeida & Lima 1994, while in Campinas it has been also reported in human faeces (Linhares 1981).…”
Section: Discussionsupporting
confidence: 88%
“…This result is similar to the behavior found in Campinas, SI=-94.30 (Linhares 1981) and Rio de Janeiro, SI=-60.1 (D'Almeida 1984); but it significantly differs from the results of Belo Horizonte, SI=4.2 (Dias et al 1984) where P. intermutans showed independence from inhabited areas and was found in the three areas, with a lower proportion in the urban area. This species showed a necrophagous behavior, also exhibited in other studies (Linhares 1981, D'Almeida 1984, D'Almeida & Lima 1994, for this reason several taxonomists have remarked its importance in forensic entomology (Carvalho et al 2000, Oliveira et al 2002, Barros et al 2008.…”
Section: Discussionsupporting
confidence: 77%
“…Particularly, Oxys. diana showed coprophagous and necrophagous habits (D'Almeida 1984, Dias et al 1984, D'Almeida and Lima 1994, Barbosa et al 2009). Our CA showed no correlation of R. columbiana and R. effrenata with any bait, although previous studies reported these species as necrophagous (Yepes-Gaurisas et al 2013, Faria 2013, Pinilla et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Previous distribution (PaPe 1996;barros et al 2008;vairo et al 2011;sousa et al 2015): Neotropical: Argentina, Brazil (Distrito Federal, Goiás, Mato Grosso, Maranhão, Minas Gerais, Paraná, Rio de Janeiro, Santa Catarina, São Paulo). Oxysarcodexia admixta has already been captured in traps baited with bovine lung and liver, human feces, fish, and domestic pig carcass (D'alMeiDa & liMa 1994;oliveira et al 2002;barros et al 2008;rosa et al 2011;vairo et al 2011;sousa et al 2015).…”
Section: Oxysarcodexia Townsend 1917mentioning
confidence: 99%